Impact of social support and presence on swift guanxi and trust in social commerce. Issue 9 (25th October 2019) - Fan, Jun; Zhou, Wangyue; Yang, Xue; Li, Boying; Xiang, Ying
Abstract : Purpose: Swift guanxi and trust can influence consumers' decision making in social commerce. What factors will influence the formation of swift guanxi and trust between buyers and sellers in social commerce has not been clearly investigated. The purpose of this paper is to identify antecedents and impacts of swift guanxi and trust in social commerce. Design/methodology/approach: An online questionnaire was used to collect the data, and Partial Least Squares Structural Equation Modeling was employed for data analysis. Social support and presence are introduced as the antecedents for swift guanxi and trust, leading to the repurchase intention (RI) and social sharing intention of customers. Findings: The results indicate that social support and presence can influence swift guanxi and trust. Social support and presence are positively associated with swift guanxi and trust which further lead to RI and social sharing intention. Practical implications: The findings can be used to guide sellers in social commerce platforms to improve their services and make good use of platform features to improve customers' perception of presence. To attract new customers and retain old customers, sellers should also build swift guanxi and trust through the recommendation and experience sharing of previous buyers on social media. Originality/value: This study combines social support theory and presence theory to investigate the factors that influence customers' purchase decision and social sharing intention in the context of social commerce in China. The integration of social support theory and presence theory explains both the social and technical factors that influence swift guanxi and trust in social commerce.